Relevansi Kewajiban Ingkar Notaris dalam Menjalankan Jabatannya (Analisis Pasal 16 Huruf f Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris) - Moh. Sodiq (Lex Renaissance, 2017)
AbstractThis study aimed to analyze the relevance and role of the notary reneges obligation MKN in providing protection to the contents secret Notary Deed related liabilities. This research is a normative approach to law(statute approach).The data used is secondary data in the form of primary legal materials, secondary law and tertiary legal materials. The results showed that the notary broken instrument liabilities as obligations mentioned in the Act, so that the obligations inherent in the task reneges notary office. MKN established to carry out the functions do coaching in order to maintain the dignity and honor of the Notary in carrying out his profession and provide protection associated with the obligation to keep the contents of the Notary Deed.Keywords: Liability dissenter, notaries, notary honorary council, UUJN-P Â